Analysis of Human Resource Management at Nasari Syariah Savings and Loan Cooperative, Lhokseumawe - Vivin Mahenrato; Muhammad Fajar Hidayat; Frengki Putra Ramansyah; Akmal (Journal of Accounting Research, Utility Finance and Digital Assets, 2025)
This study aims to analyze human resource management (HR) in the Nasari Syariah Savings and Loan Cooperative (KSP) Lhokseumawe with a focus on organizational structure, work motivation, HR training and development, and the main challenges faced. Through a field survey approach and interviews with cooperative administrators and members, it was found that the cooperative has a fairly systematic organizational structure with defined roles. In increasing work motivation, the cooperative implements a reward system that has succeeded in improving member performance. In addition, routine training and development are provided to improve the quality of sharia-based services. However, the cooperative still faces various challenges such as limited technology, difficulties in recruiting young workers, and internal conflict management. The results of this study indicate that a sharia-based strategy is an effective approach in managing cooperative HR.